Self-consciousness in female university students: the predictive role of social anxiety - Bisma Ejaz; Amina Muazzam (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: To find out the degree and direction of correlation between social anxiety and self-consciousness and to investigate the predictive role social anxiety plays in determining self-consciousness among female university students. Method: The study with cross sectional research design was conducted using non-probability purposive sampling technique to collect data. Participants of the research were university students within the age range of 18 to 26 years and were gathered from different public and private sector universities. Reliable instruments including Social Anxiety Scale, Self-consciousness Scale- R and demographic sheet were used. Descriptive statistics and linear regression analysis were employed for data analysis. Results: All the subjects in the study, 300(100%) were females with different educational qualifications ranging from Intermediate to Doctorate. The overall mean age was 21.14±2.06 years. Interesting findings revealed that age had significant inverse correlation with social anxiety (r=-0.17, p<0.01), whereas no significant relation was found between age and self-consciousness. Private self-consciousness was positively correlated with public self-consciousness (r=0.55, p<0.01), evaluation anxiety (r=.18, p<0.01), and interaction anxiety (r=0.11, p<0.05) whereas significant positive correlation was observed between public self-consciousness and all domains of social anxiety i.e. performance anxiety (r=0.21, p<0.01), interaction anxiety (r=0.29, p<0.01), and evaluation anxiety (r=0.35, p<0.01). Moreover social anxiety turned out to be a strong positive predictor of self-consciousness. Continuous...